The Problems of Using a Gender-Neutral Language in Germany - Ju. G. Timralieva; A. L. Lomonosova (Дискурс, 2025)
Introduction. The article is devoted to the problems related to the gender reform of the German language. Started on the wave of feminist movement of the 70s of the XX century, the transition to gender-neutral language in recent decades has become one of the most discussed topics in both socio-political and scientific circles in Germany, dividing politicians, lawyers, linguists and ordinary citizens into supporters and opponents of gender-neutral language.Methodology and sources. The article examines legal documents regulating the use of a gender-neutral language, highlights the opinions of participants in the discussion about gender correctness, based on the “myth of the invisible woman”, analyzes gender-oriented transformations used in German, and identifies problems related to gender-oriented language correction.Results and discussion. The starting point of linguistic distortions in the field of gender politics was the confusion of the concepts of grammatical gender (Genus), biological sex (Geschlecht) and gender (Gender/ soziales Geschlecht). The refusal of gender reform proponents to use the forms of generic masculine gender (generisches Maskulinum), which includes a wide range of meanings, and the introduction of gender-oriented transformations into the language provoked problems in the field of linguistic word usage, associated with both distortion of meaning and violation of grammatical norms of the German language.Conclusion. Gender reform has had a significant impact on various spheres of public life in Germany. The gender reform of the German language, dictated by the political agenda, has generated many linguistic and extra linguistic problems. The proposed artificial language changes aimed at achieving gender neutrality actually complicate communication and lead to a violation of the linguistic norms of the German language.